General Binomial Theorem

General Binomial Theorem

\( \begin{align} \displaystyle
(a+b)^n &= \binom{n}{0}a^nb^0 + \binom{n}{1}a^{n-1}b^1 + \cdots + \binom{n}{k}a^{n-k}b^{k} + \cdots + \binom{n}{n}a^{0}b^{n} \\
&= \sum_{k=0}^{n}\binom{n}{k}a^{n-k}b^{k}
\end{align} \)

\( \begin{align} \displaystyle
1^{\text{st}} \text{ term } T_1 &= \binom{n}{0}a^nb^0 \\
2^{\text{nd}} \text{ term } T_2 &= \binom{n}{1}a^{n-1}b^1 \\
3^{\text{rd}} \text{ term } T_3 &= \binom{n}{2}a^{n-2}b^2 \\
&\vdots \\
k^{\text{th}} \text{ term } T_k &= \binom{n}{k-1}a^{n-(k-1)}b^{k-1} \\
(k+1)^{\text{th}} \text{ term } T_{k+1} &= \binom{n}{k}a^{n-k}b^{k}
\end{align} \)

We call $\displaystyle (k+1)^{\text{th}} \text{ term } T_{k+1} = \binom{n}{k}a^{n-k}b^{k}$ as the General Term.

Example 1

Expand $(2x+3)^5$.

\( \begin{align} \displaystyle
(2x+3)^5 &= \binom{5}{0}(2x)^53^0 + \binom{5}{1}(2x)^43^1 + \binom{5}{2}(2x)^33^2 + \binom{5}{3}(2x)^23^3 + \binom{5}{4}(2x)^13^4 + \binom{5}{5}(2x)^03^5 \\
&= 2^5x^5 + 5 \times 2^4x^4 \times 3 + 10 \times 2^3x^3 \times 9 + 10 \times 2^2x^2 \times 27 + 5 \times 2x \times 81 + 243 \\
&= 32x^5 + 240x^4 + 720x^3 + 1080x^2 + 810x + 243
\end{align} \)

Example 2

Write down $5$th term of the expansion of $\displaystyle \Big(2x+\dfrac{1}{x}\Big)^{12} $.

\( \begin{align} \displaystyle
T_5 &= T_{4+1} \\
&= \binom{12}{4}(2x)^8 \Big(\dfrac{1}{x}\Big)^4 \\
&= 495 \times 256x^8 \times \dfrac{1}{x^4} \\
&= 126720x^4
\end{align} \)

Example 3

Find the coefficient of $x^6$ in the expansion of $\displaystyle\Big(x^2+\dfrac{4}{x}\Big)^{12}$.

\( \begin{align} \displaystyle
T_{k+1} &= \binom{12}{k}(x^2)^{12-k}\Big(\dfrac{4}{x}\Big)^k \\
&= \binom{12}{k}x^{24-2k}\dfrac{4^k}{x^k} \\
&= \binom{12}{k}4^k x^{24-2k-k} \\
&= \binom{12}{k}4^k x^{24-3k} \\
24-3k &= 6 \\
3k &= 18 \\
k &= 6 \\
T_{6+1} &= \binom{12}{6}4^6x^6 \\
&= 3784704
\end{align} \)
Therefore the coefficient of $x^6$ is $3784704$.

Example 4

Find the constant term in the expansion of $\displaystyle\Big(2x^3+\dfrac{1}{x}\Big)^{12}$.

\( \begin{align} \displaystyle \require{AMSsymbols} \require{color}
T_{k+1} &= \binom{12}{k}(2x^3)^{12-k}\Big(\dfrac{1}{x}\Big)^k \\
&= \binom{12}{k}2^{12-k}x^{36-3k}\Big(\dfrac{1}{x^k}\Big) \\
&= \binom{12}{k}2^{12-k}x^{36-3k-k} \\
&= \binom{12}{k}2^{12-k}x^{36-4k} \\
36-4k &= 0 &\color{red}\text{constant term}\\
k &= 9 \\
T_{9+1} &= \binom{12}{9}2^{12-9}x^0 \\
&= 1760
\end{align} \)
Therefore the constant term is $1760$.

Unlock your full learning potential—download our expertly crafted slide files for free and transform your self-study sessions!

Discover more enlightening videos by visiting our YouTube channel!

 

Algebra Algebraic Fractions Arc Binomial Expansion Capacity Common Difference Common Ratio Differentiation Double-Angle Formula Equation Exponent Exponential Function Factorise Functions Geometric Sequence Geometric Series Index Laws Inequality Integration Kinematics Length Conversion Logarithm Logarithmic Functions Mass Conversion Mathematical Induction Measurement Perfect Square Perimeter Prime Factorisation Probability Product Rule Proof Pythagoras Theorem Quadratic Quadratic Factorise Ratio Rational Functions Sequence Sketching Graphs Surds Time Transformation Trigonometric Functions Trigonometric Properties Volume




Related Articles

Responses

Your email address will not be published. Required fields are marked *